Case report: Vesiculobullous eruption with an atypical IgA deposition pattern in a patient with multiple myeloma—A case report and literature review - Li, Tong; Liu, Hongjie; Li, Wei (Frontiers in Immunology, 2023)
Cutaneous vesiculobullous eruptions associated with multiple myeloma (MM) are rare. While the development of blisters is mostly driven by amyloid deposits of paraproteins in the skin, autoimmunity may play a role. Here, we report an unusual case of a blistering patient with MM, that presented with both flaccid and tense vesicles and bullae. Direct immunofluorescence revealed IgA autoantibody deposits in the basement membrane zone (BMZ) and intercellular space of the epidermis, which displayed an atypical autoantibody deposition pattern. The patient showed rapid disease progression and died during follow-up. We performed a literature review of autoimmune bullous diseases (AIBDs) associated with MM or its precursors and found 17 previously reported cases. Together with the present case, cutaneous involvement of the skin folds is frequently reported, and mucus membranes are barely affected. IgA pemphigus, with consistent IgA monoclonality, is observed in half of the cases. Five patients displayed atypical autoantibody deposition patterns in the skin; the prognosis of these patients appeared to be poorer than that of other patients. We aim to increase our understanding of the AIBDs associated with MM or its precursors.